Analysis of Virtual Stigma and its Socio-Educational Impact: Awareness Campaigns towards People with Disabilities and Mental Disorders - García-Pérez Calabuig, María; Rodríguez-Fernández, Sonia; Galán-Casado, Diego (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Virtual social networks, key in current cultural dynamics, have an ambivalent impact. They facilitate the visibility of vulnerable groups, but they can also perpetuate prejudices and reinforce stigma in digital environments. This text analyzes various campaigns on Instagram through a mixed method. The results obtained highlight how the interactions established in the campaigns towards people with disabilities and mental disorders generate empathy, support and social demand, although it is necessary to reinforce the dissemination strategies, from a socio-educational perspective, to go beyond obtaining neutral messages. that allow greater social participation.